ANALISIS DAYA SAING EKSPOR BIJI KOPI HIJAU INDONESIA DI PASAR INTERNASIONAL TAHUN 2014-2023 - Sihombing, Devi Ananda Elisa; Widayatsari, Any (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2025)
This study aims to analyze and determine the level of competitiveness of Indonesian green coffee bean exports in the international market. This research was conducted using secondary data from various sources, including BPS (2024), International Coffee Organization (2024), and UN Comtrade (2024). The secondary data used is in the form of time series data within a period of 10 years (2014-2023). The green coffee beans that are the object of research are all types of green coffee beans. The data analysis method uses quantitative analysis methods used to analyze the level of competitiveness of Indonesian green coffee bean commodity exports in the international market which includes: Revealed Comparative Advantages (RCA) and Trade Specialization Index (ISP). Based on the analysis of the average value of Revealed Comparative Advantages (RCA) from 2014-2023 amounting to 4.90, Indonesia has a comparative advantage in trading green coffee beans in the international market. However, Indonesia's comparative advantage is still low compared to Ethiopia, Colombia, Brazil and Vietnam. Indonesia's green coffee beans have high competitiveness, with an average value of Indonesia's Index of Trade Specialization (ISP) of 0.87. This indicates that Indonesia is an exporter of green coffee bean commodities. Positive ISP results greater than 0 indicate that Indonesian green coffee bean commodities have strong competitiveness, because the value of Indonesian green coffee bean exports is greater than the value of Indonesian green coffee bean imports.